Patient outcomes following carotid endarterectomy are not adversely affected by surgical trainees' operative involvement: A retrospective cohort study. (March 2019) - Brown, Leo R.; Anderson, Jamie; Bhattacharya, Vish
Abstract: Background: Surgical training is an increasingly controversial topic. Concerns have been raised about both training opportunities becoming scarcer and poorer outcomes in operations led by surgical trainees; despite the evidence base for this being mixed. This retrospective cohort study aims to compare outcomes following carotid endarterectomy in patients who were operated on by a surgical trainee to those operated on by consultants. Materials and methods: Consecutive patients, who underwent carotid endarterectomy between 01/06/2012 and 1/12/2016, were entered into a prospectively maintained database. Patients were grouped according to whether a consultant or trainee vascular surgeon was the lead operating surgeon. Outcomes were 30-day mortality, 30-day stroke rate, operation time and complication rate. Results: One-hundred-and-twenty-one patients, with a mean age of 70.3 years, underwent carotid endarterectomy over a 4.5-year period. They were classified by the grade of the lead operating surgeon: consultant (n = 74) or registrar (n = 47). The median operative time was 117 min for consultants and 115 min for registrars with no significant difference between the two groups (p = 0.78). Three patients died in the post-op period, 2 secondary to post-operative stroke and a further 5 had nonfatal strokes. Grade of surgeon was also found to have no impact on 30- day mortality (p = 0.99) or stroke rate (p = 0.99). Sixty-six patients experienced post-operative complications, of varying severity, but no significant difference (p = 0.66) was found in incidence between trainee (57%) and consultant (53%) groups. Conclusion: Trainee involvement in carotid endarterectomy, with consultant supervision, leads to equivalent outcomes and represents a safe and useful training opportunity. Highlights: There is a paucity of contemporary research assessing the safety of trainee involvement in carotid endarterectomy. Complication rates were higher for trainees but major complications were more common with consultant led operations. 30-day mortality is slightly higher in patients operated on by a consultant but not significantly so. Carotid endarterectomy can represent a safe and useful training opportunity for an appropriately supervised trainee.